A study on the platform-pitching vibration of floating offshore wind turbines based on classical control theory. Issue 6 (December 2020) - Kakuya, Hiromu; Yoshida, Shigeo; Sato, Iku; Utsunomiya, Tomoaki
One of the issues of floating offshore wind turbines is the platform-pitching vibration generated by the blade pitch angle motion of the variable speed control. This study investigated the platform-pitching vibration based on the classical control theory using a transfer function between the generator speed and the nacelle pitch angle. This study also investigated the impact of the floating platform vibration control, which can suppress the vibration by adjusting the blade pitch angle according to the nacelle pitch angle, by using a transfer function to which floating platform vibration control is added. The stabilities of these transfer functions were determined using the Nyquist stability criterion, and the impact of the floating platform vibration control parameters was investigated using Bode diagrams.